Academic Senate Minutes 2002-10-17 - Academic Senate:::::::::
Report from Chair. Agenda amended and approved. Minutes deferred. Adult Fitness and Adapted Physical Education Concentrations approved. Report from Provost. Report from Statewide Senators and APC. Resolution on SSU Greenhouse Gasses Inventory approved. Resolution Endorsing Prop 47 approved. Constitutional Amendment regarding Article III, Section 2.2 referred to Structure & Functions.